The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2337/db07-0761
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Zinc Transporter Gene SLC30A8 Confers Resistance Against Posttransplantation Diabetes Mellitus in Renal Allograft Recipients

Abstract: OBJECTIVE—Posttransplantation diabetes mellitus (PTDM) is a major metabolic complication in renal transplant recipients, and insulin secretory defects play an important role in the pathogenesis of PTDM. The R325W (rs13266634) nonsynonymous polymorphism in the islet-specific zinc transporter protein gene, SLC30A8, has been reported to be associated with type 2 diabetes and possibly with a defect in insulin secretion. This study investigated the association between genetic variations in the SLC30A8 gene and PTDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 30 publications
5
42
0
1
Order By: Relevance
“…The unexpected interaction between ZnT-8 and CsA or calcineurin was inferred from our previous human genetic association study. 8 It has long been known that CsA treatment is correlated with the onset of PTDM, for reasons that remain to be elucidated. 3,29,30 The differing effects of two ZnT-8 variants on GSIS suggest that patients undergoing CsA immunosuppressive treatment who have the 'low-risk' ZnT-8 variant (W325) may retain insulin-secreting capacity compared with those who have the 'high-risk' variant; this may account for the protective ZnT-8 polymorphism and cyclosporin A I Kim et al effect of the W325 allele with respect to PTDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unexpected interaction between ZnT-8 and CsA or calcineurin was inferred from our previous human genetic association study. 8 It has long been known that CsA treatment is correlated with the onset of PTDM, for reasons that remain to be elucidated. 3,29,30 The differing effects of two ZnT-8 variants on GSIS suggest that patients undergoing CsA immunosuppressive treatment who have the 'low-risk' ZnT-8 variant (W325) may retain insulin-secreting capacity compared with those who have the 'high-risk' variant; this may account for the protective ZnT-8 polymorphism and cyclosporin A I Kim et al effect of the W325 allele with respect to PTDM.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Notably, SLC30A8 encodes the b-cell-specific zinc transporter-8 (ZnT-8). 7 We recently reported that the same allelic variant (which is a substitution of tryptophan for arginine at residue 325) of ZnT-8 is also associated with reduced incidence of PTDM in renal allograft recipients 8 (see Figure 1). To date, the molecular basis for PTDM has not been elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, Staiger et al demonstrated that rs13266634 is associated with reduced insulin secretion stimulated by intravenously administered glucose (54) , suggesting that rs13266634 in SLC30A8 is a crucial allele for b-cell function. Moreover, the R325W non-synonymous polymorphism in ZnT8 has been shown to protect against post-transplantation diabetes mellitus (55) , a major metabolic complication in renal transplant recipients, for which insulin-secretory defects play an important role in pathogenesis. The same polymorphism in SLC30A8, rs13266634, has eventually been associated with glycated Hb (HbA1c), a marker of long-term blood glucose levels, in a non-diabetic population (56) .…”
Section: Zinc and The Pancreatic B-cellmentioning
confidence: 99%
“…In the last decade, numerous other genetic studies for PTDM have been conducted in renal transplant recipients, and nearly 50 loci have been established as suspected loci (Table 4) [7][8][9][10]13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Polymorphisms in AIPOQ, CAPN10, CDKAL1, CDKN2A/B, HHEX, KCN11, KCNQ1, SLC30A8, and TCFL2 are known to be associated with T2DM.…”
Section: Discussionmentioning
confidence: 99%